Impact-resistant coal mine steel wire rope core flame-retardant conveyor belt covering rubber and preparation method thereof

By using modified nano white carbon black, modified aramid fiber and zinc oxide as reinforcement agents in the flame-retardant conveyor belt covering glue of wire rope core, the problems of large rolling resistance and poor impact resistance of existing conveyor belt covering glue are solved. , achieving higher mechanical properties and lower rolling resistance, extending service life and reducing energy consumption.

CN119176976BActive Publication Date: 2025-02-25XIAN ZHONGZHUANG WEINAN RUBBER PROD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411679566.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing wire rope core flame retardant conveyor belt cover has large rolling resistance, poor impact and wear resistance, resulting in short service life and high energy consumption.

Method used

Styrene butadiene rubber and natural rubber are used as the rubber main body, and modified nano-silver black, modified aramid fiber and zinc oxide are added as reinforcement agents. The preparation method of modified nano-silver black and modified aramid fibers are used. Preparation method, improve the mechanical properties and impact resistance of the covering glue, while reducing rolling resistance.

Benefits of technology

It significantly improves the mechanical properties and impact resistance of the covering glue, reduces rolling resistance, thereby extending the service life of the conveyor belt and reducing energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of conveyor belts, and in particular to a shock-resistant coal mine steel wire rope core flame-retardant conveyor belt covering rubber and a preparation method thereof. In the present invention, the shock-resistant coal mine steel wire rope core flame-retardant conveyor belt covering rubber includes components such as styrene-butadiene rubber, natural rubber, a reinforcing agent, a flame retardant, an anti-aging agent, a accelerator TMTD, an accelerator CZ and sulfur, and the reinforcing agent is composed of modified nano-white carbon black, modified aramid fiber, and zinc oxide in a mass ratio of 11-14:4-7:2-5. The present invention uses dopamine self-polymerization and a grafting reaction of a silane coupling agent to chemically modify aramid long fibers, promotes the entanglement and cross-linking between aramid fibers and a rubber matrix, selects modified nano-white carbon black, modified aramid fibers and zinc oxide to form a reinforcing agent together and add it to the rubber matrix, effectively improves the mechanical properties of the covering rubber, and reduces the rolling resistance of the covering rubber, and the aramid fiber effectively improves the impact resistance of the covering rubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conveyor belts, and in particular relates to an impact-resistant flame-retardant steel wire rope core conveyor belt covering rubber for coal mines and a preparation method thereof. Background Art

[0002] With the development of my country's coal mining industry, its mechanical automation level has been continuously improved. At the same time, due to the requirements of its conveying working environment, especially in the mining process of coal mines, the materials are not only uneven in size, but also have a large drop. The impact energy of the materials on the conveyor belt is very large. Therefore, higher requirements are placed on the impact resistance of the conveyor belt. The flame-retardant and antistatic properties of the steel wire rope core flame-retardant conveyor belt currently produced are good, but the mechanical properties of the covering rubber are low, and the outstanding performance is poor wear resistance and impact resistance, and short service life. In addition, the existing steel wire rope core flame-retardant conveyor belt has large rolling resistance and high energy consumption during use. Since the service life and energy consumption of the conveyor belt are closely related to the covering rubber, it is necessary to develop a new impact-resistant steel wire rope core flame-retardant conveyor belt covering rubber for coal mines.

[0003] The Chinese patent application document with publication number CN104910472A discloses a high-strength wear-resistant and flame-retardant conveyor belt covering rubber for coal mines and a preparation method thereof, wherein chloroprene rubber and cis-1,1-butadiene rubber are plasticized on an open mill, and then put into an internal mixer for internal mixing; reinforcing fillers, vulcanization activators, plasticizers, antioxidants and flame retardants are continuously added for internal mixing, and a first-stage mixed rubber is obtained after refining, discharging sheets and cooling with a normal temperature fan; the first-stage mixed rubber, vulcanizing agent and vulcanization accelerator are put into an internal mixer for mixing, refining, discharging sheets and cooling with a normal temperature fan to obtain the product. The covering rubber obtained by this method has good mechanical properties and wear resistance, but its rolling resistance is relatively large.

[0004] The Chinese patent application document with publication number CN115710389A discloses a low rolling resistance and high wear-resistant steel wire rope core flame-retardant conveyor belt covering rubber and its preparation method, using SiO 2 、ADP、AP、Nano-Si 3 N 4 Blending, firstly, the bio-based monomer was modified by GMA to prepare SiO 2 / ADP hybrid flame retardant reinforced material, and then macromolecular modification by CSM to prepare SiO 2 / ADP / CSM hybrid modified masterbatch, and then mixed with 70% chlorinated paraffin, antimony trioxide, and red phosphorus to form a flame retardant reinforcement system and SSBR / ENR to prepare a low rolling resistance and high wear resistant steel cord flame retardant conveyor belt covering rubber. The covering rubber prepared by this method has low rolling resistance, but its impact resistance is poor. Summary of the invention

[0005] In order to solve the technical problems existing in the related art such as large rolling resistance, poor impact resistance and wear resistance of the covering rubber, the purpose of the present invention is to provide an impact-resistant coal mine steel wire rope core flame-retardant conveyor belt covering rubber and a preparation method thereof.

[0006] In order to achieve the above object, the technical solution of the present invention is as follows:

[0007] Impact-resistant coal mine steel wire rope core flame-retardant conveyor belt covering rubber, including the following components and their weight proportions:

[0008] 60-65 parts of styrene-butadiene rubber, 30-40 parts of natural rubber, 40-45 parts of reinforcing agent, 15-20 parts of flame retardant, 10-15 parts of antioxidant, 5-8 parts of accelerator TMTD, 5-8 parts of accelerator CZ, 5-10 parts of sulfur;

[0009] The reinforcing agent is composed of modified nano-white carbon black, modified aramid fiber and zinc oxide in a mass ratio of 11-14:4-7:2-5.

[0010] In the present invention, styrene-butadiene rubber and natural rubber are selected as the rubber main body. The styrene-butadiene rubber has a low average molecular weight, a large phenyl side group is introduced into the main chain of the molecule, and there is an ethylene side group formed by a butadiene-1,2 structure, which has a large steric hindrance and a compact molecular structure, and has more excellent impact resistance; natural rubber has good mechanical properties, good flex fatigue resistance, high tear strength, good wear resistance and cold resistance. In the present invention, modified nano-white carbon black, modified aramid fiber and zinc oxide are selected to form a reinforcing agent according to a certain mass ratio and added to the rubber matrix, which effectively improves the mechanical properties of the covering rubber and reduces the rolling resistance of the covering rubber. Zinc oxide can also promote the vulcanization process of the rubber matrix.

[0011] The preparation method of the modified nano-silica is as follows: γ-aminopropyltrimethoxysilane is added to a nano-silica slurry, the powder is fully stirred and then spray-dried to obtain a powder, the powder is heated at 200-250° C. for 1.8-2.2 hours, the powder is cooled and then mixed with an ethanol aqueous solution, a pH regulator is added, the temperature is raised to 80-85° C. and then ultrasonically shaken, bis-[γ-(triethoxysilyl)propyl]tetrasulfide is added, the powder is fully reacted, aged, filtered, washed, and the modified nano-silica is obtained.

[0012] The surface of silica contains a large number of silanol groups, which causes it to form agglomerates in the rubber matrix, affecting the performance of the covering rubber. In the present invention, γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide are used to carry out composite modification of nano silica, reduce the number of silanol groups on the surface of silica, weaken the surface polarity of silica, increase the organic component, avoid stress concentration caused by the agglomeration of silica, and hinder the initiation and expansion of cracks. Among them, γ-aminopropyltrimethoxysilane can introduce amino groups on the surface of silica, and the amino groups serve as active sites. Through further modification with bis-[γ-(triethoxysilyl)propyl]tetrasulfide, long-chain molecules are introduced on the surface of silica, thereby promoting the entanglement and crosslinking between silica and the rubber matrix, thereby improving the mechanical properties of the covering rubber. In addition, it was found during the research that γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide can also change the steric hindrance of the rubber chain and effectively reduce the rolling resistance of the covering rubber.

[0013] Furthermore, in the preparation method of modified nano-silica, the nano-silica slurry is a mixture of nano-silica and deionized water, and the mass percentage of nano-silica is 10%-13%; the mass ratio of the nano-silica, γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is 23-27:7-10:2-5.

[0014] Furthermore, in the preparation method of modified nano-silica, the mass percentage of the ethanol aqueous solution is 85%-90%, and the amount of the ethanol aqueous solution is 3-5 times the mass of the powder; the pH adjuster is glacial acetic acid or citric acid, and the pH value of the pH adjuster added to the system is 4-5.

[0015] Furthermore, the preparation method of the modified aramid fiber is: add trihydroxymethylaminomethane to the dopamine hydrochloride aqueous solution until the pH value is 8.0-8.5, add aramid fiber, stir and heat to 30-35°C, keep warm for 1-2 hours, then add N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane under stirring, fully react, centrifuge, wash and dry to obtain modified aramid fiber.

[0016] Aramid fiber has excellent specific strength, elastic modulus and toughness, and can be charred at high temperature. It is a high-performance reinforcing fiber with flame retardant properties. However, the surface of aramid fiber is smooth and chemically inert, thus reducing its interfacial bonding performance with the rubber matrix material. In the present invention, aramid fiber is placed in an aqueous solution of dopamine hydrochloride. Under alkaline conditions, dopamine undergoes a self-polymerization reaction and adheres to the surface of the aramid fiber through van der Waals forces, hydrogen bonds, and π-π stacking to form a polydopamine coating. Then, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is added to be grafted to the surface of polydopamine, thereby introducing organic long-chain molecules on the surface of the aramid fiber, promoting the entanglement and crosslinking between the aramid fiber and the rubber matrix, thereby improving the mechanical properties of the covering rubber. In addition, the aramid fiber forms a fiber network structure in the rubber matrix material, which can effectively improve the impact resistance of the covering rubber.

[0017] Furthermore, in the preparation method of the modified aramid fiber, the mass ratio of the aramid fiber, dopamine hydrochloride and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is 17-21:10-13:5-9.

[0018] Furthermore, in the method for preparing the modified aramid fiber, the mass percentage of the dopamine hydrochloride aqueous solution is 5%-10%.

[0019] Furthermore, the flame retardant is one or more of zinc borate, aluminum hydroxide, ammonium polyphosphate, and red phosphorus.

[0020] Furthermore, the antioxidant is one or more of antioxidant RD, antioxidant 4020, antioxidant 4010NA, and microcrystalline wax.

[0021] The present invention also provides a method for preparing the impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel wire rope core, comprising the following steps:

[0022] S1: Add styrene-butadiene rubber and natural rubber to an open mixer and mix them evenly, then add a reinforcing agent, a flame retardant and an antioxidant, tap the rubber until the rubber is evenly mixed, then add the rubber to an internal mixer, heat it to 85-90°C, rotate the rotor at 80-85rpm, and perform plasticizing to obtain a rubber compound;

[0023] S2: The rubber material obtained in step S1 is naturally cooled, and then accelerator TMTD, accelerator CZ and sulfur are added, and the rubber material is placed on a double-roll open mill for eight-shaped cutting until the mixing is uniform, and the rubber material is cut into sheets after four triangle packing to obtain a mixed rubber;

[0024] S3: The vulcanization time of the rubber compound obtained in step S2 is tested by a flat vulcanizer, and the rubber compound is vulcanized at a vulcanization temperature of 145-150° C. to obtain an impact-resistant flame-retardant conveyor belt covering rubber for a coal mine steel wire rope core.

[0025] Compared with the prior art, the impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel wire rope provided by the present invention and the preparation method thereof have the following technical advantages:

[0026] (1) In the present invention, modified nano-silica, modified aramid fiber and zinc oxide are selected in a certain mass ratio to form a reinforcing agent and added to the rubber matrix, which effectively improves the mechanical properties of the covering rubber and reduces the rolling resistance of the covering rubber. Zinc oxide can also promote the vulcanization process of the rubber matrix;

[0027] (2) The present invention uses dopamine self-polymerization and silane coupling agent grafting reaction to chemically modify the aramid long fibers, thereby improving the surface activity of the aramid long fibers and the bonding performance between the aramid long fibers and the rubber matrix, promoting the entanglement and cross-linking between the aramid fibers and the rubber matrix, thereby improving the mechanical properties of the covering rubber; in addition, the aramid fibers form a fiber network structure in the rubber matrix material, which can effectively improve the impact resistance of the covering rubber;

[0028] (3) In the present invention, styrene-butadiene rubber and natural rubber are selected as the rubber main body. Styrene-butadiene rubber has large steric hindrance, compact molecular structure and better impact resistance; natural rubber has good mechanical properties, good flexural fatigue resistance, high tear strength, good wear resistance and cold resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a process flow chart of the covering rubber for impact-resistant coal mine steel cord flame-retardant conveyor belts;

[0030] Figure 2 Schematic diagram of the digital drop weight low-speed impact test device.

[0031] Figure 2 In the figure, 1 is an iron plate, 2 is a guide rail, 3 is an electromagnet suction plate, 4 is an accelerometer, 5 is a force sensor, 6 is a shading sheet, 7 is a punch, 8 is an infrared speed meter, 9 is a fixture, and 10 is a test piece. DETAILED DESCRIPTION

[0032] The technical scheme of the present invention is clearly and completely described below in conjunction with specific embodiments. The specific embodiments described are only partial embodiments of the present invention, rather than limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present invention.

[0033] The process flow chart of the impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel cord core in this specific embodiment is as follows: Figure 1 shown.

[0034] Example 1

[0035] Impact-resistant coal mine steel wire rope core flame-retardant conveyor belt covering rubber, including the following components and their weight proportions:

[0036] 60 parts of styrene-butadiene rubber, 40 parts of natural rubber, 40 parts of reinforcing agent, 15 parts of ammonium polyphosphate, 10 parts of antioxidant RD, 5 parts of accelerator TMTD, 5 parts of accelerator CZ, and 5 parts of sulfur; the reinforcing agent is composed of modified nano-silica, modified aramid fiber, and zinc oxide in a mass ratio of 11:4:2.

[0037] The preparation method of the modified nano-silica is as follows: γ-aminopropyltrimethoxysilane is added to a nano-silica slurry with a mass percentage of 10% (the nano-silica slurry is a mixture of nano-silica and deionized water), the mixture is fully stirred and then spray-dried to obtain a powder, the powder is heated at 200° C. for 2.2 hours, the powder is cooled and then mixed with an ethanol aqueous solution with a mass percentage of 85%, the amount of the ethanol aqueous solution being 3 times the mass of the powder, a pH regulator (glacial acetic acid or citric acid) is added to adjust the pH value of the system to 4, the temperature is raised to 80° C. and then ultrasonically shaken, bis-[γ-(triethoxysilyl)propyl]tetrasulfide is added, the mixture is fully reacted, aged, filtered, and washed to obtain the modified nano-silica; the mass ratio of the nano-silica, γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is 23:7:2.

[0038] The preparation method of the modified aramid fiber is as follows: add trihydroxymethylaminomethane to a 5% by mass aqueous solution of dopamine hydrochloride until the pH value is 8.0, add aramid fiber, stir and heat to 30°C, keep warm for reaction for 1 hour, then add N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane under stirring, fully react, centrifuge, wash and dry to obtain the modified aramid fiber; the mass ratio of the aramid fiber, dopamine hydrochloride and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is 17:10:5.

[0039] The method for preparing the impact-resistant coal mine steel wire rope core flame-retardant conveyor belt covering rubber comprises the following steps:

[0040] S1: Add styrene-butadiene rubber and natural rubber to an open mixer and mix them evenly, then add a reinforcing agent, ammonium polyphosphate and antioxidant RD, tap the rubber until the rubber is evenly mixed, then add it to an internal mixer, heat it to 85°C, rotate the rotor at 80 rpm, and plasticize to obtain a rubber compound;

[0041] S2: The rubber material obtained in step S1 is naturally cooled, and then accelerator TMTD, accelerator CZ and sulfur are added, and the rubber material is placed on a double-roll open mill for eight-shaped cutting until the mixing is uniform, and the rubber material is cut into sheets after four triangle packing to obtain a mixed rubber;

[0042] S3: The vulcanization time of the rubber mix obtained in step S2 is tested by using a flat vulcanizer, and the rubber is vulcanized at a vulcanization temperature of 145° C. to obtain an impact-resistant flame-retardant conveyor belt covering rubber for a coal mine steel wire rope core.

[0043] Example 2

[0044] Impact-resistant coal mine steel wire rope core flame-retardant conveyor belt covering rubber, including the following components and their weight proportions:

[0045] 65 parts of styrene-butadiene rubber, 30 parts of natural rubber, 45 parts of reinforcing agent, 20 parts of zinc borate, 15 parts of antioxidant 4020, 8 parts of accelerator TMTD, 8 parts of accelerator CZ, and 10 parts of sulfur; the reinforcing agent is composed of modified nano-silica, modified aramid fiber, and zinc oxide in a mass ratio of 14:7:5.

[0046] The preparation method of the modified nano-silica is as follows: γ-aminopropyltrimethoxysilane is added to a nano-silica slurry with a mass percentage of 13% (the nano-silica slurry is a mixture of nano-silica and deionized water), the powder is fully stirred and then spray-dried to obtain a powder, the powder is heated at 250° C. for 2.2 hours, the powder is cooled and then mixed with a 90% ethanol aqueous solution with a mass percentage of 5 times the mass of the powder, a pH regulator (glacial acetic acid or citric acid) is added to adjust the pH value of the system to 5, the temperature is raised to 85° C. and ultrasonically vibrated, bis-[γ-(triethoxysilyl)propyl]tetrasulfide is added, the reaction is fully carried out, the mixture is aged, the mixture is filtered and washed to obtain the modified nano-silica; the mass ratio of the nano-silica, γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is 27:10:5.

[0047] The preparation method of the modified aramid fiber is as follows: add trihydroxymethylaminomethane to a 10% by mass aqueous solution of dopamine hydrochloride until the pH value is 8.5, add aramid fiber, stir and heat to 35°C, keep warm for reaction for 2 hours, then add N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane under stirring, fully react, centrifuge, wash and dry to obtain the modified aramid fiber; the mass ratio of the aramid fiber, dopamine hydrochloride and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is 21:13:9.

[0048] The method for preparing the impact-resistant coal mine steel wire rope core flame-retardant conveyor belt covering rubber comprises the following steps:

[0049] S1: Add styrene-butadiene rubber and natural rubber to an open mixer and mix them evenly, then add a reinforcing agent, zinc borate and antioxidant 4020, tap the rubber until the rubber is evenly mixed, then add it to an internal mixer, heat it to 90°C, rotate the rotor at 85rpm, and plasticize to obtain a rubber compound;

[0050] S2: The rubber material obtained in step S1 is naturally cooled, and then accelerator TMTD, accelerator CZ and sulfur are added, and the rubber material is placed on a double-roll open mill for eight-shaped cutting until the mixing is uniform, and the rubber material is cut into sheets after four triangle packing to obtain a mixed rubber;

[0051] S3: using a flat vulcanizer to test the vulcanization time of the rubber mix obtained in step S2, and vulcanizing the rubber at a vulcanization temperature of 150° C. to obtain an impact-resistant flame-retardant conveyor belt covering rubber for a coal mine steel cord.

[0052] Example 3

[0053] Impact-resistant coal mine steel wire rope core flame-retardant conveyor belt covering rubber, including the following components and their weight proportions:

[0054] 63 parts of styrene-butadiene rubber, 37 parts of natural rubber, 42 parts of reinforcing agent, 18 parts of red phosphorus, 13 parts of antioxidant 4010NA, 7 parts of accelerator TMTD, 7 parts of accelerator CZ, and 8 parts of sulfur; the reinforcing agent is composed of modified nano-silica, modified aramid fiber, and zinc oxide in a mass ratio of 13:6:4.

[0055] The preparation method of the modified nano-silica is as follows: γ-aminopropyltrimethoxysilane is added to a nano-silica slurry with a mass percentage of 12% (the nano-silica slurry is a mixture of nano-silica and deionized water), the powder is fully stirred and then spray-dried to obtain a powder, the powder is heated at 230° C. for 2.0 hours, and after cooling, it is mixed with an ethanol aqueous solution with a mass percentage of 88%, the amount of the ethanol aqueous solution being 4 times the mass of the powder, a pH regulator (glacial acetic acid or citric acid) is added to adjust the pH value of the system to 4.5, the temperature is raised to 83° C. and ultrasonically vibrated, bis-[γ-(triethoxysilyl)propyl]tetrasulfide is added, the reaction is fully carried out, aging, suction filtration, washing, and the modified nano-silica is obtained; the mass ratio of the nano-silica, γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is 25:9:4.

[0056] Furthermore, the preparation method of the modified aramid fiber is as follows: add trihydroxymethylaminomethane to an 8% by mass aqueous solution of dopamine hydrochloride until the pH value is 8.3, add aramid fiber, stir and heat to 32°C, keep warm for reaction for 1.5 hours, then add N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane under stirring, react fully, centrifuge, wash and dry to obtain modified aramid fiber; the mass ratio of the aramid fiber, dopamine hydrochloride and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is 19:12:7.

[0057] The method for preparing the impact-resistant coal mine steel wire rope core flame-retardant conveyor belt covering rubber comprises the following steps:

[0058] S1: Add styrene-butadiene rubber and natural rubber to an open mixer and mix them evenly, then add a reinforcing agent, red phosphorus and antioxidant 4010NA, tap the rubber until the rubber is evenly mixed, then add it to an internal mixer, heat it to 87°C, rotate the rotor at 83rpm, and plasticize to obtain a rubber compound;

[0059] S2: The rubber material obtained in step S1 is naturally cooled, and then accelerator TMTD, accelerator CZ and sulfur are added, and the rubber material is placed on a double-roll open mill for eight-shaped cutting until the mixing is uniform, and the rubber material is cut into sheets after four triangle packing to obtain a mixed rubber;

[0060] S3: The vulcanization time of the rubber mix obtained in step S2 is tested by using a flat vulcanizer, and the rubber is vulcanized at a vulcanization temperature of 148° C. to obtain an impact-resistant flame-retardant conveyor belt covering rubber for a coal mine with a steel cord core.

[0061] Comparative Example 1

[0062] The formula and preparation method of the covering rubber described in this comparative example are similar to those of Example 3. The difference between this comparative example and Example 3 is that the reinforcing agent described in this comparative example consists of modified nano-silica gel, modified aramid fiber, and zinc oxide in a mass ratio of 1:7:10.

[0063] Comparative Example 2

[0064] The formula and preparation method of the covering rubber in this comparative example are similar to those in Example 3. The difference between this comparative example and Example 3 is that this comparative example uses an equal amount of nano-silica to replace the modified nano-silica in the reinforcing agent.

[0065] Comparative Example 3

[0066] The formula and preparation method of the covering glue described in this comparative example are similar to those of Example 3. The difference between this comparative example and Example 3 is that an equal amount of γ-aminopropyltriethoxysilane is used instead of γ-aminopropyltrimethoxysilane in the preparation method of the modified nano-white carbon black in this comparative example.

[0067] Comparative Example 4

[0068] The formula and preparation method of the covering rubber described in this comparative example are similar to those of Example 3. The difference between this comparative example and Example 3 is that an equal amount of γ-methacryloxypropyltrimethoxysilane is used instead of bis-[γ-(triethoxysilyl)propyl]tetrasulfide in the preparation method of the modified nano-white carbon black in this comparative example.

[0069] Comparative Example 5

[0070] The formula and preparation method of the covering glue described in this comparative example are similar to those of Example 3. The difference between this comparative example and Example 3 is that in the preparation method of the modified nano-silica in this comparative example, a pH regulator is added to adjust the pH value of the system to 6.5.

[0071] Comparative Example 6

[0072] The formula and preparation method of the covering glue in this comparative example are similar to those of Example 3. The difference between this comparative example and Example 3 is that an equal amount of deionized water is used instead of the dopamine hydrochloride aqueous solution in the preparation method of the modified aramid fiber in this comparative example.

[0073] Comparative Example 7

[0074] The formula and preparation method of the covering rubber described in this comparative example are similar to those of Example 3. The difference between this comparative example and Example 3 is that an equal amount of γ-aminopropyltriethoxysilane is used instead of N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane in the preparation method of the modified aramid fiber in this comparative example.

[0075] Test example

[0076] Mechanical property test: The covering rubbers prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 7 were tested for tensile strength and elongation at break according to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber"; the tear strength was tested according to GB / T 529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber (trouser-shaped, right-angled and crescent-shaped specimens)", and the tear test used a right-angled tear specimen;

[0077] Impact resistance test: The impact resistance test of the cover rubbers prepared in Examples 1 to 3 was carried out using a digital drop hammer low-speed impact test device. Figure 2 As shown, the impact load when the covering rubber is penetrated is recorded during the test;

[0078] Wear resistance test The cover rubbers prepared in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 7 were subjected to wear resistance test according to GB / T 1689-2014 "Determination of wear resistance of vulcanized rubber", and the wear volume was recorded;

[0079] Rolling resistance test: using a viscoelasticity analyzer, the dynamic mechanical properties of the cover rubbers prepared in Examples 1-3 and Comparative Examples 1-7 were measured, and the tan (δ) value at 60° C. during the temperature scan was recorded under the dynamic strain condition of a frequency of 10 Hz;

[0080] The test results are shown in Table 1.

[0081] Table 1 Performance test results

[0082]

[0083] As shown in Table 1, the tensile strength of the impact-resistant coal mine steel wire rope core flame-retardant conveyor belt covering rubber provided by the present invention is 21.3-24.1MPa, the elongation at break is 439.7%-502.4%, the tear strength is 51.4-53.2KN / m, the impact load at breakdown is 11587.6-13264.2N, and the wear volume is 43-54mm 3 , the rolling resistance is 0.099-0.123, which shows that the impact-resistant coal mine steel wire rope core flame retardant conveyor belt covering rubber provided by the present invention has good mechanical properties, wear resistance and impact resistance. Among them, the impact-resistant coal mine steel wire rope core flame retardant conveyor belt covering rubber prepared in Example 3 has the best performance in all aspects and is the best embodiment of the present invention.

[0084] Compared with Example 3, Comparative Example 1 changes the mass ratio of each component of the reinforcing agent, but the mechanical properties of the obtained covering rubber deteriorate and the rolling resistance increases, which shows that the dosage of each component in the reinforcing agent in the present invention has been optimized; Comparative Example 2 uses an equal amount of nano-silica to replace the modified nano-silica in the reinforcing agent, but the mechanical properties of the obtained covering rubber deteriorate and the rolling resistance increases, which shows that the composite modification of nano-silica by using γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide in the present invention can promote the entanglement and crosslinking between silica and the rubber matrix, thereby improving the mechanical properties of the covering rubber and effectively reducing the rolling resistance of the covering rubber; Comparative Example 3 uses an equal amount of γ-aminopropyltriethoxysilane to replace γ-aminopropyltrimethoxysilane, but the mechanical properties of the obtained covering rubber deteriorate and the rolling resistance increases, which shows that γ-aminopropyltrimethoxysilane can introduce amino groups on the surface of silica, which is the key to modifying nano-silica; Comparative Example 4 uses an equal amount of In the present invention, γ-methacryloxypropyltrimethoxysilane is used to replace bis-[γ-(triethoxysilyl)propyl]tetrasulfide. In comparative example 5, the pH value of the reaction system is changed, but the mechanical properties of the obtained covering rubber are deteriorated and the rolling resistance is increased. This indicates that under acidic conditions, bis-[γ-(triethoxysilyl)propyl]tetrasulfide can introduce long-chain molecules on the surface of silica, thereby promoting the entanglement and crosslinking between silica and the rubber matrix, thereby improving the mechanical properties of the covering rubber, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide can promote the entanglement and crosslinking between silica and the rubber matrix, thereby improving the mechanical properties of the covering rubber. )propyl] tetrasulfide and γ-aminopropyltrimethoxysilane can work together to reduce the rolling resistance of the covering rubber; Comparative Example 6 uses an equal amount of deionized water instead of the dopamine hydrochloride aqueous solution, and Comparative Example 7 uses an equal amount of γ-aminopropyltriethoxysilane instead of N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, but the mechanical properties of the prepared covering rubber deteriorate, and the impact load at the time of breakdown is reduced. This is due to the poor modification effect of the aramid fiber and the poor dispersion performance in the rubber.

[0085] The above embodiments are only preferred embodiments of the present invention, and are not intended to limit the present invention. Any person skilled in the art shall not modify the above embodiments without violating the spirit and scope of the present invention. Therefore, any modification, equivalent substitution and improvement made by those skilled in the art under the technical concept of the present invention shall still be covered by the claims of the present invention.

Claims

1. An impact-resistant flame-retardant conveyor belt covering rubber for coal mines, characterized in that: It includes the following components and their weight parts: 60-65 parts of styrene-butadiene rubber, 30-40 parts of natural rubber, 40-45 parts of reinforcing agent, 15-20 parts of flame retardant, 10-15 parts of antioxidant, 5-8 parts of accelerator TMTD, 5-8 parts of accelerator CZ, 5-10 parts of sulfur; The reinforcing agent is composed of modified nano-white carbon black, modified aramid fiber, and zinc oxide in a mass ratio of 11-14:4-7:2-5; the preparation method of the modified aramid fiber is: adding trihydroxymethylaminomethane to a dopamine hydrochloride aqueous solution until the pH value is 8.0-8.5, adding aramid fiber, stirring and heating to 30-35° C., keeping the temperature for reaction for 1-2 hours, and then adding N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane under stirring, fully reacting, centrifuging, washing and drying to obtain the modified aramid fiber; The preparation method of the modified nano-silica is as follows: γ-aminopropyltrimethoxysilane is added to a nano-silica slurry, and the mixture is spray-dried after being fully stirred to obtain a powder, and the powder is heated at 200-250° C. for 1.8-2.2 hours, and the powder is mixed with an ethanol aqueous solution after being cooled, and a pH regulator is added to adjust the pH value of the system to 4-5, and the mixture is heated to 80-85° C. and ultrasonically vibrated, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is added, and the mixture is fully reacted, aged, filtered, and washed to obtain the modified nano-silica.

2. The impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel cord according to claim 1 is characterized in that: The nano-silica slurry is a mixture of nano-silica and deionized water, wherein the mass percentage of the nano-silica is 10%-13%; the mass ratio of the nano-silica, γ-aminopropyltrimethoxysilane and bis-[γ-(triethoxysilyl)propyl]tetrasulfide is 23-27:7-10:2-5.

3. The impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel wire rope according to claim 1 is characterized in that: The mass percentage of the ethanol aqueous solution is 85%-90%, and the amount of the ethanol aqueous solution is 3-5 times the mass of the powder; the pH regulator is glacial acetic acid or citric acid.

4. The impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel cord according to claim 1 is characterized in that: The mass ratio of the aramid fiber, dopamine hydrochloride and N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane is 17-21:10-13:5-9.

5. The impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel cord according to claim 1 is characterized in that: The mass percentage of the dopamine hydrochloride aqueous solution is 5%-10%.

6. The impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel cord according to claim 1 is characterized in that: The flame retardant is one or more of zinc borate, aluminum hydroxide, ammonium polyphosphate and red phosphorus.

7. The impact-resistant flame-retardant conveyor belt covering rubber for coal mines according to claim 1 is characterized in that: The antioxidant is one or more of antioxidant RD, antioxidant 4020, antioxidant 4010NA, and microcrystalline wax.

8. The method for preparing the impact-resistant flame-retardant conveyor belt covering rubber for coal mine steel cord according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Add styrene-butadiene rubber and natural rubber to an open mixer and mix them evenly, then add a reinforcing agent, a flame retardant and an antioxidant, tap the rubber until the rubber is evenly mixed, then add the rubber to an internal mixer, heat it to 85-90°C, rotate the rotor at 80-85rpm, and perform plasticizing to obtain a rubber compound; S2: The rubber material obtained in step S1 is naturally cooled, and then accelerator TMTD, accelerator CZ and sulfur are added, and the rubber material is placed on a double-roll open mill for eight-shaped cutting until the mixing is uniform, and the rubber material is cut into sheets after four triangle packing to obtain a mixed rubber; S3: The vulcanization time of the rubber compound obtained in step S2 is tested by a flat vulcanizer, and the rubber compound is vulcanized at a vulcanization temperature of 145-150° C. to obtain an impact-resistant flame-retardant conveyor belt covering rubber for a coal mine steel wire rope core.

Citation Information

Patent Citations

  • High-strength wear-resistant flame-retardant conveying belt cover rubber for coal mine and preparation method thereof

    CN104910472A

  • Low-rolling-resistance high-wear-resistance steel wire rope core flame-retardant conveying belt covering rubber and preparation method thereof

    CN115710389A

  • Packing leather cup rubber for brake wheel cylinder of automobile and preparation method thereof

    CN103102526A

  • Anti-cutting conveyor belt cover rubber and preparation method thereof

    CN112724479A